Importancia del uso de microorganismos del género Trichoderma sp. para el control biológico de los cultivos - Pazmiño Miranda, Jeyson Alexi (2020)
This document was developed in order to strengthen knowledge regarding the importance of the use of microorganisms of the genus Trichoderma sp. for the biological control of crops. Biological control is the use of organisms that are natural enemies of a pest or pathogen, in order to reduce or eliminate its harmful effects on plants or their products, used empirically in agriculture since its inception. The main reason why many agricultural products are not completely destroyed by pests and diseases is the natural presence of biological control agents: organisms capable of antagonizing pests or pathogens, reducing their harmful effects. The information that was developed according to the collected investigations of scientific articles, texts, magazines, newspapers, presentations, conferences and virtual pages. The search was subsequently subjected to the analysis and summary technique where everything related to the study topic was dealt with. Based on the foregoing, it was determined that continuous development and innovation promoted research to develop biological products that effectively control pests and diseases of different crops; biological fungicide products based on beneficial microorganisms of the genus Trichoderma sp. help protect plants from different soil diseases and in turn manages to nourish the roots for optimal growth and development of the plantation and biological products allow the use of chemical pesticides to be reduced, therefore they persevere the health of the human beings and avoid contamination of the environment and soil.